Os acordos internacionais de trabalho como um novo instrumento regulatório das relações trabalhistas no âmbito transnacional: em busca da efetivação do conceito de trabalho decente - Carreira, Cristiane de Mattos (2024)
The processes of globalization directly affected the dynamics of labor regulation, which was based on the direct action of States and on international regulation through International Conventions signed by the ILO and other international organizations. This form of regulation, however, no longer meets current economic and social demands, given the emergence of a new relevant social actor: transnational companies. This thesis aims to analyze the asymmetry of power between transnational companies, States and the ILO, as well as answer the following questions: has the evolution of society impacted labor regulation? What are the main heteronomous and autonomous forms of international labor regulation? How are international labor law standards applied? What can be done based on the current system to guarantee the effectiveness of labor standards? As a solution to the problem presented, the creation of a new regulatory instrument is proposed, aiming to promote decent work, based on the concept of dialogue and social consultation